Модифікація методу лінійної інтерполяції для розв’язування систем нелінійних рівнянь - Бартіш, М.Я.; Ковальчук, О.В.; Коркуна, Н.М. (Математичне та комп'ютерне моделювання. Серія: Фізико-математичні науки, 2010)
Досліджується новий підхід до побудови методів розв’язування нелінійних систем. Даний метод базується на методах спуску та лінійної інтерполяції. Досліджено швидкість збіжності. Проведено чисельні експерименти на тестових задачах, та порівняно з базовими методами. In this paper a new way to the creation of the method for solving system of nonlinear equations is being researched, which is based on steepest descent and the linear interpolation methods. We have proved theorem where the convergence of the proposed method is justified and the rate of convergence is established. Numeral experiments have been conducted on the test problems and they have been compared of the basic method. The conclusions on the possibilities application of method have been made.